Nutrient uptake under combined drought and salinity stress in hexaploid wheat species - Khan, Mohd. Kamran (Frontiers in Plant Science, 2025)
Wheat is an important crop that often suffers from combined drought and salinity stress in agricultural fields, which adversely affects its growth, yield, and nutrient uptake. Understanding the response of genotypes to this combined stress is crucial to developing resilient cultivars. Nutrient uptake patterns in plants under stress not only reveal the physiological effects but also reflect their adaptive strategy and tolerance potential. Neglected and underutilized wheat species with high genetic diversity offer a valuable resource to explore different traits under combined stresses. Notably, no study has thoroughly assessed nutrient uptake in different hexaploid wheat species under combined drought and salinity stress. Thus, this study provides new insights into the individual and combined effects of drought and salinity stresses on nutrient uptake and accumulation of 30 hexaploid wheat genotypes of seven different species grown in a hydroponic system. The combined stress had a synergistic negative effect on nutrient accumulation in wheat genotypes as compared to single stresses. While species-based genetic variability was observed in individual stresses, a greater genotypic diversity was noticed under combined stress. A considerable genotypic variation ranging from 33.6% to 62.6% was observed in traits such as root-shoot phosphorus, manganese, zinc, as well as root copper, iron, and dry weight, while traits like shoot calcium, iron, potassium, and dry weight showed lower genotypic variation (8.3% to 25.8%). Among the studied genotypes, Tc4 (PI 164160, Kanak, India) was the best performing genotype across all three stress conditions, followed by Ta3 (CItr 17028, CAR 1101, Chile) and Tsh2 (PI 42013, India). The patterns of nutrient accumulation proposed that combined stress encompasses a complex interaction of multiple stress pathways. The results yielded valuable insights underscoring the significance of nutrient profiling as a critical component of breeding frameworks for climate-resilient wheat.